Pengaruh Budaya Organisasi Terhadap Organizational Citizenship Behavior (OCB) Melalui Kepuasan Kerja dan Komunikasi pada Sekolah Luar Biasa Se Kota Banjarbaru - Irfan Stiyan Noor; Ahmad Suriansyah; Noorhapizah Noorhapizah (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
The purpose of this study is to analyze the influence of organizational culture on organizational citizenship behavior through job satisfaction and communication in SLB in Banjarbaru City. This research is a correlational research with descriptive-quantitative methods. The study population was all SLB teachers in Banjarbaru City as many as 138 people with a sample of 103 respondents taken by random sampling technique. Data collection using questionnaire instruments and data analysis using descriptive analysis, classical assumption test, multiple linear regression analysis and path analysis. The results showed that Organizational Culture has an influence on Organizational Citizenship Behavior (OCB) with a correlation coefficient value of 0.436 and a positive direction; Job Satisfaction has an influence on Organizational Citizenship Behavior (OCB) with a correlation coefficient value of 0.359 and a positive direction; Communication has an influence on Organizational Citizenship Behavior (OCB) with a correlation coefficient value of 0.246 and a positive direction; Organizational Culture has an influence on Job Satisfaction with a correlation coefficient value of 0.656 and a positive direction; Organizational Culture has an influence on Communication with a correlation coefficient value of 0.757 and a positive direction; Organizational Culture has an influence through Job Satisfaction on Organizational Citizenship Behavior (OCB) with ZSobel values of 5.86936 > ZScore 1.96; Organizational Culture has an influence through Communication on Organizational Citizenship Behavior (OCB) with the results of ZSobel values of 5.92750 > ZScore 1.96. Keywords: Communication, Job Satisfaction Organizational Culture, Organizational Citizenship Behavior